Assentamentos rurais : o campo das sociabilidades em transformação. O caso dos assentados do Nova Pontal - Ramiro, Patrícia Alves (Universidade Federal de São Carlos, 2008)
The present work intends to contribute for quarrel on the agrarian reform adopting as bias the interpretation of the process of construction of the social identity generated by the adoption of new forms of sociability in the agricultural way, created for the possibility of permanence or return to the field through the implantation of rurals projects of settlements. In the field of the agricultural sociability, we look for to detect which the values gifts in the ideal and real actions of these people who pass, after conquest of a land piece, to coexist daily in one same space and presenciam difficulties and similar initial chances, even so have particular histories of life. Therefore, nor the Brazilian agricultural settlement origin and nor the profile of the seated population are similar, have distinctions not only enter the different projects of settlements, but also in the internal profile of one exactly settlement and, in this way, the perceptions that after construct the conquest of the land expresses this multiplicity of inserted social citizens in the program of agrarian reform. The methodology adopted for the understanding of the process of construction of these new identities appeared through the agricultural settlements is the concept-type of Gemeinschaft and Gesellschaft (community and society) formulated by Ferdinand Tönnies, whose complementary and contradictory nature allows in them to analyze the different forms of social organization, as the moment and the movement of the wills that characterize these two concepts central offices. The interpretation of the native categories that give sensible to the Inter life and inner life of the seated ones if of the one through the understanding of the values (dialectic component of the social nature of the human being) that, however attracts, however moves away people ones from the others. On the basis of the carried through empirical research in the project of settlement New Pontal, located in the city of Rosana, in the region of the Pontal of the Paranapanema, we could, saw study of the predominant sociabilities, to delineate the concept of agricultural society as modeller of the style of predominant life in the agricultural area (re) constructed by the agrarian reform.
Keywords: Reforma agrária; Assentamentos rurais; Sociabilidade; Identidade; Sociologia rural; CIENCIAS SOCIAIS APLICADAS